Prieto: Yorùbá kingship in colonial Cuba during the age of revolutions - Lovejoy, Henry ca. 20./21. Jh. (Envisioning Cuba, 2018)
Introduction: slave, soldier, and Lucumí leader -- Badagry -- The golden age -- La Habana -- Batallón de morenos -- Ṣàngó Tẹ̀ Dún -- New Lucumí from Òyó -- Lucumí war -- Prieto's disappearance -- Conclusion: Prieto's legacy